DEVELOPMENT OF EFFERVESCENT GRANULE OF CORN MILK, SUPPLEMENTED WITH PROBIOTICS LACTOBACILLUS STRAIN SHIROTA - Hiola, Reni; Tungadi, Robert (International Journal of Applied Pharmaceutics, 2018)
Objective: One of the materials which can be formulated into probiotics drink is corn milk. It has nutrient contents such as vitamin A, B, C, minerals, and fibres. The objective of this study was to develop and evaluate the probiotic drink of corn milk which was formulated into an effervescent granule. Methods: The first step was carried out to make corn extract with the addition of Lactobacillus strain Shirota and incubated 24 h at 40 Â°C to gain corn milk. After that, corn milk was centrifuged to get filtrate and dried by oven 40 Â°C for 2 d to gain dry powder. Then corn milk powder was formulated into effervescent granule (3 formulas) using different ratio of acids. The method which used in making effervescent granule of corn milk was wet granulation. All formulas were done evaluations including physical and chemical properties of granule and hedonic test. Results: The results showed that formula 1 (only citric acid 23.84%) gave unsatisfactory results particularly on the evaluation tests such as LOD 9.64%, dissolution time 3.25 min, moisture content 10.67% and hedonic test which did not meet the requirements. Otherwise, formula 2 (only tartaric acid 23.84%) and formula 3 (citric acid 7.94% and tartaric acid 15.9% combination) showed satisfactory results for all evaluation tests of granules. Particularly formula 3 gave pH 5 on pH test which was the same as pH lactic acid for fermentation and LOD 4.34%, MC 4.53%, Ïb 0.53 g/ml, Ït 0.62 g/ml and hedonic test around 80%. Conclusion: Formula 3 was the best formulation based on the evaluation and the stability of corn milk effervescent granule.